The Law and the Lady - Collins, Wilkie, 1824-1889 (Salt Lake City, UT : Project Gutenberg, 1999)
"The Law and the Lady" by Wilkie Collins is a detective and sensation novel published in 1875. When Valeria Brinton discovers her new husband has concealed his true identity, she uncovers a disturbing truth: he was tried for murdering his first wife by arsenic poisoning. The Scottish verdict of "not proven" leaves him under permanent suspicion. Determined to prove his innocence and save their marriage, Valeria embarks on her own investigation, encountering the brilliant but unstable Miserrimus Dexter, whose genius may hold the key to the mystery. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Law_and_the_Lady_(novel)
Release date is 1999-02-01
Produced by John Hamm, James Rusk, Janet Blenkinship and David Widger
Keywords: England -- Social life and customs -- 19th century -- Fiction; Married people -- Fiction; Mystery fiction